2021
DOI: 10.3389/fcell.2021.700482
|View full text |Cite
|
Sign up to set email alerts
|

To Better Generate Organoids, What Can We Learn From Teratomas?

Abstract: The genomic profile of animal models is not completely matched with the genomic profile of humans, and 2D cultures do not represent the cellular heterogeneity and tissue architecture found in tissues of their origin. Derived from 3D culture systems, organoids establish a crucial bridge between 2D cell cultures and in vivo animal models. Organoids have wide and promising applications in developmental research, disease modeling, drug screening, precision therapy, and regenerative medicine. However, current organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 165 publications
(280 reference statements)
0
6
0
Order By: Relevance
“…Li et al. 65 also suggested establishing guidelines for evaluating the quality and effectiveness of organoids to minimize the differences in organoids among laboratories. In humans, genetic and environmental diversity cannot be eliminated from donor-derived organoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al. 65 also suggested establishing guidelines for evaluating the quality and effectiveness of organoids to minimize the differences in organoids among laboratories. In humans, genetic and environmental diversity cannot be eliminated from donor-derived organoids.…”
Section: Discussionmentioning
confidence: 99%
“…3). Li et al 65 discussed several limitations in constructing human organoids, including the diversity in the nature and morphology of the organoids produced. Toxicologic pathologists are expected to actively participate in finding solutions to address the diversity of ex vivo-constructed organoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report demonstrated that cartilaginous organoids made out of pluripotent stem cell-derived promoted the scaffold-free healing of long bone defects with critical size [ 35 ]. Furthermore, the development of blood vessels and communication with surrounding tissue can lead to greater development and more wide use of the organoids in bone regeneration [ 41 ]. The control of the coating material for the culturing dish and loading density of the cells may influence the characteristics of the organoids [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first case of MCTO was reported by Johannes Scultetus in 1659 after the autopsy of a young woman who died of an ovarian tumor and was described as a “dermoid cyst of the ovary”, while Rudolf Virchow introduced the term “teratoma” derived from the Greek word “teras,” meaning monster, in 1863 [ 5 , 6 ]. The etiology, as well as the pathophysiology, of the MCTO, is not fully known; this is particularly true in consideration of their ability to differentiate into tissue cells and, in some cases, and they also develop into organ systems [ 7 ].…”
Section: Introductionmentioning
confidence: 99%